HUBUNGAN KULIATAS PRODUK, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK EIGER DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Ifan Susianto; Siti Soeliha; Ayu Dita Windra Ciptasari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to examine the effects of product quality, brand image, and promotion on the purchase decisions of Eiger products, with trust serving as an intervening variable, among students of the Faculty of Economics and Business at Abdurrachman Saleh University, Situbondo. This research employed a quantitative approach, utilizing a survey with 88 respondents chosen through purposive sampling. Data were processed using SmartPLS 3.0 to test validity, reliability, and the relationships between variables through path analysis. The results show that product quality, brand image, and promotion have a positive and significant effect on trust. Product quality significantly influences purchase decisions, whereas brand image and promotion do not have a direct significant effect. Trust is found to be a significant mediating variable in the relationship between promotion and purchase decisions. However, it does not significantly mediate the relationships between product quality or brand image and purchase decisions. These findings highlight the importance of building consumer trust to enhance the effectiveness of Eiger’s marketing strategies.